The Effect of Digital Transformation and Digital Innovation on Business Performance Through Digital Leadership at PT Bank NTT in The Society 5.0 Era - Doto, Steffidya K.M Bale; Fanggidae, Rolland E.; Fanggidae, Apriana H.J (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to examine how digital leadership mediates the effect of digital transformation and digital innovation on business performance at PT Bank NTT in the Society 5.0 era. This research employs a quantitative method using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach to test both direct and indirect relationships among independent, mediating, and dependent variables. The data used are primary data collected through questionnaires distributed to employees of Bank NTT. The sampling technique applied is purposive sampling based on specific criteria. The results of the direct effect testing indicate that digital transformation, digital innovation, and digital leadership have a positive and significant effect on business performance, while digital transformation and digital innovation also have a positive effect on digital leadership. The results of the indirect effect testing show that digital leadership is able to mediate the influence of digital transformation and digital innovation on business performance.